INCREASE OF WORKING EFFICIENCY OF MACHINES OF INGOTS CONTINUOUS CASTING AS A RESULT OF INTRODUCTION OF CRYSTALLIZERS SLEEVES «VM-SINUS» - G. I. Nikolaev; A. V. Drozdov; S. A. Berkovich (Литьë и металлургия)
The ways of increase of operation efficiency of the ingots continuous casting machine for production of round ingots as a result of introduction of sleeves of crystallizers «VM-sinus» are considered.